Vocal Models and Musical Rhythm in Central Sri Lanka - Eshantha Peiris (Analytical Approaches to World Music)
While the use of drumming to communicate verbal phrases has been well studied in the context of Africa, recent research has drawn more attention to the ways in which rhythmic-melodic patterning in South Asian instrumental musics relate to verbal or vocal models. In this article, I contribute to the discourse about vocal models and musical rhythm in South Asia by analyzing three musical piece-types from Sri Lanka associated with Buddhist performance traditions. Through these examples I examine how drumming has been employed as efficacious speech to invoke supernatural intervention, and how non-lexical vocables can model syllable patterns for texted poetry; I also draw attention toward similar cultural phenomena from across the broader geographic region, suggesting hitherto unsuspected historical relationships between communities.